Successful management of a case of delayed post-operative recovery under general anesthesia due to endotracheal tube defect and malfunction in a case of massive abdominal teratoma in 2-month-old infant - Suvidha Sood,; Anoj,; Megha Soni, (Indian Journal of Case Reports, 2021)
Endotracheal tube (ETT) connector is an important part of the airway equipment, especially in intubated neonates and pediatric patients, which if narrow and improper sized, due to manufacturing defect, can compromise airway safety by causing high airway resistance, inadequate gaseous exchange, and ventilation through the ETT causing respiratory acidosis and hypercapnia resulting in a delayed recovery of infants. Hence, equipment check before anesthesia is mandatory especially in extremes age groups such as neonate and pediatric population. We, hereby, report the case of a blocked ETT defect in a 2-month-old child posted for massive abdominal teratoma.